Genome-wide association study −Driven drug repositioning for the treatment of insomnia - Rahmat Dani Satria; Wirawan Adikusuma; Usi Sukorini; Devy Eka Avitasari; Indra Sari Kusuma Harahap; Mohammad Hendra Setia Lesmana; Lalu Muhammad Irham; Nur Imma Fatimah Harahap; Pranindya Rinastiti; Donytra Arby Wardhana; Richardus Wisnandito Prabasaktya; Chiou-Feng Lin; et al. (Journal of Genetic Engineering and Biotechnology)
Insomnia is a prevalent sleep disorder characterized by difficulty initiating or maintaining sleep, leading to severe health complications, increased mortality, and substantial socioeconomic burdens. Despite therapeutic advancements, effective pharmacological interventions remain limited, necessitating alternative approaches for drug discovery. This study aimed to identify potential therapeutic targets for insomnia by integrating gene network analysis, genomic data, and bioinformatics-driven drug repurposing strategies, aligning with the United Nations’ Sustainable Development Goal (SDG) 3: Good Health and Well-being. Insomnia-associated Single Nucleotide Polymorphisms (SNPs) were retrieved from the GWAS catalog, yielding 3,952 loci. Insomnia risk genes were identified by linking these loci to proximal SNPs (r2 ≥ 0.8) in Asian populations using HaploReg v4.2, resulting in 1,765 candidate genes. A bioinformatics pipeline incorporating ten functional annotations and drug-gene interaction was employed to prioritize gene targets and identify novel repurposed drugs with potential biological relevance to insomnia. Drug-Gene Interaction Database (DGIdb) analysis identified seven druggable targets among 27 biologically significant insomnia risk genes, corresponding to 12 existing drugs. Notably, NRXN1 emerged as a highly promising target due to its strong functional annotation score and its known interaction with Duloxetine hydrochloride and nicotine polacrilex. This study underscores the potential of bioinformatics-driven gene network analysis in identifying drug repurposing candidates for insomnia. Further experimental validation is warranted to elucidate the therapeutic mechanisms of NRXN1 modulation in insomnia treatment.